Brain Imaging Changes in Patients Recovered From COVID-19: A Narrative Review - Huang, Yan; Ling, Qiong; Manyande, Anne; Wu, Duozhi; Xiang, Boqi (Frontiers in Neuroscience, 2022)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused several outbreaks of highly contagious respiratory diseases worldwide. The respiratory symptoms of Coronavirus Disease-19 (COVID-19) have been closely monitored and studied, while the central nervous system (CNS) and peripheral system (PNS) lesions induced by COVID-19 have not received much attention. Currently, patients with COVID-19-associated encephalopathy present with dizziness, headache, anxiety and depression, stroke, epileptic seizures, the Guillain-Barre syndrome (GBS), and demyelinating disease. The exact pathologic basis for these neurological symptoms is currently not known. Rapid mutation of the SARS-CoV-2 genome leads to the appearance of SARS-CoV-2 variants of concern (VOCs), which have higher infectivity and virulence. Therefore, this narrative review will focus on the imaging assessment of COVID-19 and its VOC. There has been an increase in technologies, such as [18F]fluorodeoxyglucose positron emission tomography (18F-FDG-PET) and functional magnetic resonance imaging (fMRI), that have been used to observe changes in brain microstructure over time in patients with COVID-19 recovery. Medical imaging and pathological approaches aimed at exploring the associations between COVID-19 and its VOC, with cranial nerve and abnormal nerve discharge will shed light on the rehabilitation process of brain microstructural changes related to SARS-CoV-2, and aid future research in our understanding of the treatment and prognosis of COVID-19 encephalopathy.